“This house is so lonely!”: Home, Belonging, and Identity in Memoirs of Loss and Grief - Małecka, Katarzyna A. (Text Matters: A Journal of Literature, Theory and Culture, 2024)
This analysis explores select autobiographical representations of relationships the bereaved develop with their surroundings in the context of a major death-related loss. After a significant loss, the concepts of home, belonging, and identity are redefined, and the grieving self needs to revise its assumptive worldview to adjust to these changes. Drawing parallels between bereavement research and grief memoirs, three main themes are analyzed: 1. How hitherto familiar spaces feel both welcome and unwelcome to the bereaved; 2. How loss influences culinary settings and domestic routines; and 3. How financial factors and relocation uproot the griever’s identity and sense of belonging.